Effects of European Union Enlargement on the Viability of Hydroprocessed Esters and Fatty Acids Production Usage in Diesel Engines - J. F. Liow; H. Chan; C. T. Chong; J.-H. Ng (Journal of the Society of Automotive Engineers Malaysia, 2022)
The utilization of crude oil-derived diesel fuel has undeniably contributed to the adverse environmental effects in the European Union (EU). To align with the European Council’s mandate to increase the shares of renewable energy consumed, it is important to facilitate the implementation of renewable diesel fuel in the EU automotive sector. Using an Energy-Water-Food (EWF) nexus approach, a data-driven model was established to investigate the sustainability of Hydroprocessed Esters and Fatty Acids (HEFA), which has dual usage as diesel engine fuel and sustainable aviation fuel (SAF). In this model, a total of three EU enlargement phases and Brexit (namely, EU-12, EU-28, EU-27, and one projected enlargement), were considered. The analysis was conducted on 43 selected European countries, including six Eurasian states. The scenario combinations cover three different subsidy schemes at the same crude oil price of €100/bbl. When a full subsidy scheme is applied, the Czech Republic, Germany, Hungary, Ireland, Turkey, and Ukraine can have profitable HEFA production. However, only Czech Republic has the potential to produce HEFA profitably under the partially subsidized condition if all the exported palm oils are retained in the country. Most of the European countries have their sustainable HEFA production limited by crude oil price and feedstock quantity, attributed to the high processing cost and tight feedstock supplies. The future biofuel and waste energy shares of the enlarged EU (EU-43) are shown to be the worst, followed by EU-12, EU-28, and EU-27 (after Brexit). Despite the low contributions of HEFA as a diesel engine fuel to meet the EU renewable energy regulations, however, it will be prudent to include HEFA as part of the mid-term energy solution mix.